Location, Quality, and Price Drive Home Purchases in Indonesia: Lokasi, Kualitas, dan Harga Mendorong Pembelian Rumah di Indonesia - Muhammad Afif Syaifudin; Misti Hariasih; Dewi Komala Sari (Academia Open, 2024)
This study examines the influence of location, product quality, and price on purchasing decisions at Graha Candi Pratama housing in Indonesia. Despite extensive research on housing purchase decisions, the unique contributions of these factors at Graha Candi Pratama have not been thoroughly explored. A quantitative approach was employed, sampling 96 homeowners via questionnaires, with data analyzed using SPSS 25. Results indicate that favorable location, high product quality, and affordable pricing significantly impact consumer decisions. Developers are advised to consider modern trends, cultural habits, and continually improve design and amenities while maintaining affordable pricing to attract buyers. Highlight: Location Impact: Proximity to amenities and transport influences purchase decisions. Product Quality: High-quality construction and variety increase buyer satisfaction. Price Affordability: Competitive pricing enhances housing project attractiveness. Keywoard: Housing purchase decision, location, product quality, price, consumer behavior